Biological consequences of infection of Escherichia coli B by alkylated T7 bacteriophage. - Karska-Wysocki, B (1981)
Alkylation of T7 bacteriophage considerably delayed phage development and reduced the phage's killing action on host cells. Only a small fraction of infected cells produced phage. For these phages, the latent period was markedly prolonged but the burst was equivalent to or only slightly lower than that of untreated phage. In the progeny of alkylated phage, there was an increase in the fraction of defective particles as well as a change in their morphology. These data show that infection with alkylated T7 bacteriophage is to a large degree abortive; hence, biological consequences of this infection are very different from those characteristic of a normal virus infection.